2019
DOI: 10.1159/000498893
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Extract Activates Tartrate-Resistant Acid Phosphatase-Positive Macrophage

Abstract: Background: It has been reported that smoking is one of the strongest positive risk factors for abdominal aortic aneurysms (AAAs). Although many studies have been directed to decipher the effect of smoking on AAA, its effect on macrophage activation has not yet been explored. Objectives:We have reported the importance of osteoclastogenesis (OCG) in aneurysm formation. Therefore, we examined the effect of cigarette smoking on OCG and arterial aneurysmal formation by using cigarette smoke extract (CSE) in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…At present, the pathogenesis of AAA is mainly attributed to inflammatory cell infiltration, the destruction of elastin and collagen in the media and adventitia, biological changes in smooth muscle cells and angiogenesis (180,181). Studies have confirmed that cigarette extracts induce the conversion of macrophages to osteoclasts through the classic RANKL-RANK pathway, upregulate the expression of NFATc1, promote macrophage activation, and induce the expression of the osteoclastogenesis-related proteases TRAP, cathepsin K and MMP-9 (129)(130)(131). Second, CSE also enhances the inflammatory response through the NF-kB pathway, which leads to the activation of macrophages and increased expression of MCP-1, MMP-9, IL-8, and TNF-α.…”
Section: Smoking-related Molecular Mechanismsmentioning
confidence: 99%
“…At present, the pathogenesis of AAA is mainly attributed to inflammatory cell infiltration, the destruction of elastin and collagen in the media and adventitia, biological changes in smooth muscle cells and angiogenesis (180,181). Studies have confirmed that cigarette extracts induce the conversion of macrophages to osteoclasts through the classic RANKL-RANK pathway, upregulate the expression of NFATc1, promote macrophage activation, and induce the expression of the osteoclastogenesis-related proteases TRAP, cathepsin K and MMP-9 (129)(130)(131). Second, CSE also enhances the inflammatory response through the NF-kB pathway, which leads to the activation of macrophages and increased expression of MCP-1, MMP-9, IL-8, and TNF-α.…”
Section: Smoking-related Molecular Mechanismsmentioning
confidence: 99%
“… 13 TRAP-positive macrophages produce various matrix metalloproteinases (MMPs) such as MMP-2 (gelatinase A), MMP-9 (gelatinase B), MMP-12 (macrophage metalloelastase), and MMP-14 (MT1-MMP). 14 , 15 Therefore, TRAP-positive lung macrophages might display some molecular signatures of osteoclast differentiation regulated by the RANKL signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In AAAs, we found that approximately 50% of macrophages form RANKL–RANK complexes on the cell surface that trigger activation of nuclear factor of activated T cells c1 (NFATc1) and expression of OC-related genes including MMP-9. Previous research in a mouse model has shown that cigarette smoke extract (CSE) treatment significantly exacerbates OCL macrophages and AAA formation, accompanied by upregulation of hypoxia-inducible factor-1 alpha [ 28 ].…”
mentioning
confidence: 99%